2013
DOI: 10.3233/jad-121975
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thinning in Dementia Associated with Parkinson's Disease, Dementia with Lewy Bodies, and Alzheimer's Disease

Abstract: Optical coherence tomography is a simple, high-resolution technique to quantify the thickness of retinal nerve fiber layer (RNFL). Previous studies have shown that degenerative changes occur in optic nerve fibers and are manifested as thinning of RNLF in patients with Alzheimer's disease (AD). However, there are no studies on the thickness of the RNLF in other types of dementia, such as dementia with Lewy bodies and dementia associated with Parkinson's disease. In this study, patients fulfilling diagnostic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(145 citation statements)
references
References 34 publications
7
135
2
1
Order By: Relevance
“…The disadvantage of OCT is that it cannot be used to distinguish between the different types of dementia because of low sensitivity. MorenoRamos have characterized retinal changes across different types of dementia including dementia with AD, dementia with Lewy bodies and Parkinson's-associated dementia (Moreno Romos et al 2013). No statistically significant differences in RFNL thickness between different types of dementia have been observed.…”
Section: Results Of Review Of Systematic Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantage of OCT is that it cannot be used to distinguish between the different types of dementia because of low sensitivity. MorenoRamos have characterized retinal changes across different types of dementia including dementia with AD, dementia with Lewy bodies and Parkinson's-associated dementia (Moreno Romos et al 2013). No statistically significant differences in RFNL thickness between different types of dementia have been observed.…”
Section: Results Of Review Of Systematic Evidencementioning
confidence: 99%
“…Whether the retina can be used to make a specific diagnosis of (Harazny et al 2011) and adaptive optic retinal imaging (Moreno Romos et al 2013), provide a detailed analysis of the retina including the retinal oxygen concentration, blood flow, foveal capillary network and choroidal vasculature enabling retinal vasculature screening to be used as a method for population screening of AD (Moreno Romos et al 2013). The retinal amyloid test is a potential screening test that can complement the currently used tests and could potentially be delivered as part of regular eye checks.…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not a correlation exists between retinal changes and severity of dementia also remains a controversial issue. While most OCT studies did not show correlation between Minimal Mental State Examination (MMSE) and peripapillary RNFL thinning (Table 2), one TD-OCT study reported correlation between MMSE scores and macular volume [44], and more recent studies using SD-OCT have indeed reported a significant correlation between MMSE scores and RNFL thickness [50,66,72,76,77]. Studies comparing changes in RNFLT in MCI and AD (Table 2) have also yielded conflicting results, although the majority reported no statistically significant differences between MCI and AD patient groups [46,47,54,77].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…184 Retinal nerve fibre layer (RNFL) abnormalities in AD and controls have been studied using optical coherence tomography (OCT), a simple, high resolution method of quantifying the thickness of the RNFL. 185 This technique was originally used to study glaucoma and non-glaucomatous neuropathies. 186 A number of studies of RNFL using OCT have been carried out in AD.…”
Section: Posterior Segment Of the Eyementioning
confidence: 99%